Peran Perempuan dalam Meningkatkan Ekonomi Keluargamelalui Pemanfaatan Potensi Lokal (Pengelolaan Sagu di Desa Sungai Bemban Kab. Kubu Raya) - Ita Nurcholifah (Raheema, 2016)
The nation’s prosperity and wealth could be acknowledged from the economy sector. To improve the economy sector of one nation could not be performed half-hearted. It would need the support of all citizen, especially the smallest entity of the society – a family. The married women could also help their husband to enhance the household finance. The effort, in addition, would be effective by processing the local natural resources. Furthermore, through the local resources utilization, the housewives especially could enhance their economy.Besides, the Sago management processed by the farmer of Sago at Sungai Bemban village is stil lack in any aspects. Because they only work on half materials called “Sagu Basah”. Therefore, they need a guidance to create an excellent product of sago that could be a chance of business.